Relatório de estágio curricular supervisionado em medicina veterinária - áreas de anestesiologia e cirurgia de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The Supervised Curricular Internship in Veterinary Medicine (ECSMV) undertaken at Universidade Estadual Paulista (FCAV-UNESP), at the Veterinary Hospital “Governador Laudo Natel” of the Faculty of Agricultural and Veterinary Sciences located in Jaboticabal-SP. From January 5 to March 4, 2016, an internship in the field of small animal anesthesiology was supervised by Prof. Dro Andre Escobar, totaling 336 hours. Subsequently, from March 7 to May 6, 2016, the internship in the small animal surgery area was supervised by Prof. Dr. Paola Castro Moraes, totaling 336 hours. This report aims to describe the activities carried out and monitored by the academic Lucas Oliveira de Andrades during the period of the ECSMV, as well as to present a case of interest chosen by the academic, with Professor Maria Lígia de Arruda Mistieri as the advisor.
Report of supervised internship in veterinary medicine - areas of anesthesiology and small animal surgery
Keywords: Medicina veterinária; Cirurgia veterinária; Cirurgia de pequenos animais; Anestesia veterinária; Veterinary medicine; Veterinary surgery; Small animal sugery; Veterinary anesthesia; CNPQ::CIENCIAS AGRARIAS